Metabolic capabilities of cytochrome P450 enzymes in Chinese liver microsomes compared with those in Caucasian liver microsomes - Yang, Junling; He, Minxia M.; Niu, Wei; Wrighton, Steven A.; Li, Li; Liu, Yang; Li, Chuan (British journal of clinical pharmacology, 2012)
WHAT IS ALREADY KNOWN ABOUT THIS SUBJECT • The mean catalytic activities of CYP1A2, CYP2A6, CYP2D6, CYP2E1 and CYP3A4 in human liver microsomes (HLM) of Japanese origin were found to be lower than the corresponding mean values of Caucasian HLM, but the distribution patterns of data in these studies were not well addressed. • Interindividual variations in metabolic activities of Chinese HLM samples were reported for CYP1A2, CYP2C9, CYP2D6 and CYP3A4, but little is known about the difference in CYP activities between Chinese and Caucasian HLM samples. • The vast majority of the preceding studies were based on the measurement of metabolite formation rates at a certain fixed substrate concentration, rather than enzyme kinetic analyses. WHAT THIS STUDY ADDS • Significant differences in metabolic capability were observed for CYP1A2, CYP2C9, CYP2C19 and CYP2E1 with the median values lower for the Chinese HLM samples vs. the Caucasian samples, which were associated with differences in Michaelis constant or maximum velocity. • Despite negligible differences in metabolic capability for CYP2A6, CYP2B6, CYP2C8, CYP2D6 and CYP3A, Michaelis constant of CYP2B6 appeared to have a significant ethnic difference. AIM The most common causes of variability in drug response include differences in drug metabolism, especially when the hepatic cytochrome P450 (CYP) enzymes are involved. The current study was conducted to assess the differences in CYP activities in human liver microsomes (HLM) of Chinese or Caucasian origin. METHODS The metabolic capabilities of CYP enzymes in 30 Chinese liver microsomal samples were compared with those of 30 Caucasian samples utilizing enzyme kinetics. Phenacetin O‐deethylation, coumarin 7‐hydroxylation, bupropion hydroxylation, amodiaquine N‐desethylation, diclofenac 4′‐hydroxylation (S)‐mephenytoin 4′‐hydroxylation, dextromethorphan O‐demethylation, chlorzoxazone 6‐hydroxylation and midazolam 1′‐hydroxylation/testosterone 6β‐hydroxylation were used as probes for activities of CYP1A2, CYP2A6, CYP2B6, CYP2C8, CYP2C9, CYP2C19, CYP2D6, CYP2E1 and CYP3A, respectively. Mann‐Whitney U test was used to assess the differences. RESULTS The samples of the two ethnic groups were not significantly different in cytochrome‐b5 concentrations but were significantly different in total CYP concentrations and NADPH‐P450 reductase activity (P < 0.05). Significant ethnic differences in intrinsic clearance were observed for CYP1A2, CYP2C9, CYP2C19 and CYP2E1; the median values of the Chinese group were 54, 58, 26, and 35% of the corresponding values of the Caucasian group, respectively. These differences were associated with differences in Michaelis constant or maximum velocity. Despite negligible difference in intrinsic clearance, the Michaelis constant of CYP2B6 appeared to have a significant ethnic difference. No ethnic difference was observed for CYP2A6, CYP2C8, CYP2D6 and CYP3A. CONCLUSIONS These data extend our knowledge on the ethnic differences in CYP enzymes and will have implications for drug discovery and drug therapy for patients from different ethnic origins.